Implementation Of Carrier-Based Simple Boost Pulse Width Modulation (PWM) For Z-Source Inverter (ZSI) Using Field Programming Gate Array (FPGA) - Muhammad, M; Rasin, Zulhani; Jidin, Auzani (IOP Publishing, 2017)
In recent years, the research on the Z-source inverter (ZSI) has received a wide acceptance due to its attractive solution for example in the renewable energy interface that requires voltage boost capability. The conventional inverter circuit based on the SPWM technique for example does not able to fully utilize its DC input voltage to produce a greater output voltage. The ZSI shoot-through implementation in high switching frequency requires a processor with fast sampling and high precision. In simulation, this can be easily carried out with the available advanced engineering software. In the hardware implementation however, the processor used is not only handle the switching, but also needs to read the data obtained by the sensor, voltage and current control, information display etc. This limits the capacity that can be used to implement the switching fast sampling with high precision. The aims of this work are to implement high precision of carrier-based simple boost PWM for ZSI using FPGA and to verify its real time hardware implementation. The high precision of PWM control algorithm based on the FPGA platform is verified by comparing the simulation results with the experimental results for different modulation index and boost factor, and a good agreement is concluded. It is observed that the application of FPGA reduces complexity, increases speed and the design of the switching technique can be altered without having to modify the hardware implementation.